THE EFFECT OF PRESS TEMPERATURE ON SOME MECHANICAL PROPERTIES OF WOOD BASED COMPOSITE PANELS (Innovation in Woodworking Industry and Engineering design, 2026)
This research investigated the effect of press temperature on some mechanical properties of wood based composite panels. For this purpose, three layers wood based composite panels were produced from a mixture of scots pine (Pinus sylvestris L.) and black pine wood (Pinus nigra V.) particles at certain ratios utilizing urea formaldehyde (UF) adhesive. All panels were tested for mechanical properties; modulus of rupture, modulus of elasticity, internal bond strength. The results have shown that press temperature were affected on the mechanical properties of the manufactured wood based composite panels. When the press temperature was increased the mechanical properties were also increased. However high press temperature may destroy the natural color of composite panel and increase manufacture cost. The manufactured composite panels may use as industrial design engineering material such as furniture, sliding doors, pool tables, floor underlayment, cupboards, home constructions, wall linings, cabinets and stair treads.